INVESTIGATION OF DISSOLVED SULPHATE IN VARIOUS GEOTHERMAL FIELDS OF SUMATRA USING OXYGEN AND SULPHUR ISOTOPES - E. Ristin Pujiindiyati; Zainal Abidin (Indonesian Journal of Chemistry, 2006)
There are at least 30 high temperature systems; eleven active volcanoes, five degassing volcanoes and one caldera volcano controlled by Sumatra Fault Zone over a length of 1700 km. To understand this geothermal field system, some information about geochemistry including isotope composition in its fluid is needed. Sulphur-34 and oxygen-18 isotopes in dissolved sulphate pair have been used to determine the origin of acidic fluid of sulphate and to evaluate the process involved. The fluids from eight hot springs, two fumaroles, four deep wells and crater have been collected in along Sumatra geothermal fields. Sulphur-34 (d 34S (SO4), 0/00 CDT) and oxygen-18 (d 18O (SO4), 0/00 SMOW) in sulphate is analyzed according to Robinson-Kusakabe and Rafter method, respectively. The d 34S (SO4) values from Sibayak wells are more enriched of 16.8 0/00 to 18.2 0/0 that may indicate the dissolution of anhydrite minerals or isotope partitioning in hydration of SO2. The d 34S (SO4) values from two fumaroles (Pusuk Bukit - North Sumatra and Rantau Dadap - South Sumatra) are at depleted value of -0.150/00 and 1.80/00, those are close to d 34S from magmatic sulphur.  In general, the d 34S (SO4) of springs spread in a wide range of 5.250/00 to14.20/00 and show a mixing process between atmospheric sulphate and sulphate from deep wells. The d 18O (SO4) from wells exhibits depleted value around -3.60/00 suggesting that 87.5% of sulphate oxygen is derived from groundwater oxygen and 12.5% is derived from atmospheric molecular oxygen in sulphide oxidation reaction. In the other hand, hot springs (except Semurup), crater and fumaroles have enriched value of d 18O (SO4). These enriched values suggest that a higher percentage of atmospherically derived oxygen compared to those from the depth.